D‐series resolvins inhibit murine abdominal aortic aneurysm formation and increase M2 macrophage polarization. Issue 12 (12th September 2016) - Pope, Nicolas H.; Salmon, Morgan; Davis, John P.; Chatterjee, Anuran; Su, Gang; Conte, Michael S.; Ailawadi, Gorav; Upchurch, Gilbert R.
ABSTRACT: The role of resolvins in abdominal aortic aneurysm (AAA) has not been established. We hypothesized that treatmentwithD‐series resolvins (RvD2 or RvD1)would attenuate murine AAA formation through alterations in macrophage polarization and cytokine expression. Male C57/B6 mice ( n = 9 per group) 8 to 12 wk old received RvD2 (100 ng/kg/treatment), RvD1 (100 ng/kg/treatment), or vehicle only every third day beginning 3 d before abdominal aorticperfusionwith elastase asprevention. Aortaswere collected 14 d after elas taseperfusion. Cytokine analysis ( n = 5 per group) or confocal microscopy ( n = 4 per group) was performed. In a separate experiment, RvD2 was provided tomicewith small AAAs 3 d after elastase treatment ( n = 8 per group). Additionally, apolipoprotein E knockoutmice treatedwith angiotensin II (1000 ng/kg) were treated with RvD2 or vehicle alone ( n = 10 per group) in a nonsurgical model of AAA. To determine the effect of RvD2 on macrophage polarization, confocal staining for macrophages, M1 and M2 macrophage subtypes, α‐actin, and DAPI was performed. Mean aortic dilationwas 966 13% for vehicle‐treated mice ≤57 × 9.7% for RvD2‐treated mice, and 61 ± 11% for RvD1‐treated mice ( P < 0.0001). Proinflammatory cytokines macrophage chemotactic protein 1, C‐X‐C motif ligand 1, and IL‐1β were significantly elevated in control animals compared to RvD2‐ and RvD1‐treated animals ( P < 0.05), resulting in a reduction of matrix metalloproteinase 2 and 9 activity in resolvin‐treated mice in both elastase and angiotensin II models. Treatment of existing small AAAs with RvD2 demonstrated a 25%reduction in aneurysm size at d 14 compared to vehicle alone ( P = 0.018). Confocal histology demonstrated a prevalence of M2 macrophages within the aortic medium in mice treated with RvD2. Resolvin D2 exhibits a potent protective effect against experimental AAA formation. Treatment with RvD2 significantly influences macrophage polarization and decreases several important proinflammatory cytokines. Resolvins and the alteration of macrophage polarization represent potential future targets for prevention of AAA.—Pope, N.H., Salmon, M., Davis, J. P., Chatterjee, A., Su, G., Conte, M. S., Ailawadi, G., Upchurch, G. R., Jr. D‐series resolvins inhibit murine abdominal aortic aneurysm formation and increase M2 macrophage polarization. FASEB J. 30, 4192–4201 (2016). www.fasebj.org